Green Bio-Analytical Study of Gabapentin in Human Plasma Coupled with Pharmacokinetic and Bioequivalence Assessment Using UPLC-MS/MS - Rehab Moussa Tony; Mohamed A. El Hamd; Mohammed Gamal; Safaa F. Saleh; Nujud Maslamani; Wejdan T. Alsaggaf; Mohamed B. El-Zeiny (Separations, 2023)
Gabapentin (GAB) is a cyclohexane acetic acid, structurally related to the neurotransmitter gamma-aminobutyric acid (GABA), and considered the principal inhibitory neurotransmitter in the central nervous system (CNS) of mammals. An ultra-performance liquid chromatography–tandem mass spectrophotometry (UPLC-MS/MS) method for assessing pregabalin (PRE) in human plasma, was developed and validated, via PRE usage as an internal standard. The plasma underwent protein precipitation using methanol, prior to analysis. Chromatographic separation was completed using a mobile phase of methanol: 0.1% formic acid solution, (65:35, v/v), at a flow rate of 0.2 mL/min, with an isocratic approach, on an Agilent Eclipse plus column (50 × 2.1 mm and 1.8 μm), in 1.6 min of running time. An Agilent triple quadrupole was used for mass analysis, to detect the ion transitions for GAB and PER, respectively, at m/z of 172.1 → 154.1 and 160.10 → 142.10. The calibration curve, over the linear range of 0.050–10.0 μg/mL, showed a high correlation coefficient, r = 0.9993. The limits of detection and quantitation were 13.37 ng/mL and 40.52 ng/mL, respectively, based on the standard deviation and slope equation. The results for intra- and inter-day measurement accuracy and precision were in acceptable ranges. The method was extended into the assessment of oral administrations of GAB at different doses, of one 600 mg/tablet and two capsules (each one of them has 300 mg of GAB), to volunteers who were used in pharmacokinetics and bioequivalent studies. The AGREE assessment tool was used to visualize the proposed method’s greenness degree, which revealed a high AGREE rating score, supporting the accepted method’s greenness profile.